A revision of the family Typhlotanaidae Sieg 1984 (Crustacea: Tanaidacea) with the remarks on the Nototanaidae Sieg, 1976 - Błażewicz-Paszkowycz, Magdalena (Zootaxa, 2007)
Recent tanaidacean material collected from Antarctic waters, primarily during the ANDEEP expeditions of 2002 and 2005, includes a number of new taxa attributable to the families Nototanaidae and Typhlotanaidae sensu Sieg. Analysis of this material has exposed a problem with the recent contention of the two families, and has revealed consistent morphological trends which support the distinction of these two families. In the present paper, examination of both museum specimens and newly-collected material, has allowed a re-analysis based on a series of detailed morphological observations, resulting in a new definition of the families Typhlotanaidae Sieg, 1984 with the establishment of five new genera (Hamatipeda n. gen., Larsenotanais n. gen., Pulcherella n. gen., Torquella n. gen., Typhlamia n. gen.), a the description of thirteen new species, the redescription of fifteen species, and the construction of keys for the determination of typhlotanaid genera and of the species of three newly-erected genera.